Feasibility study of a cold gas-propelled autonomous surveying vehicle for lunar environments - Jagdish, Nikita; Gunter, Brian C. (Frontiers in Space Technologies, 2025)
With impending plans for establishing the first long-term lunar base camp, there is a need to find sustainable habitation sites on the Moon. Discovered in 2009, lunar lava tubes have shown potential for base sites and have been proposed for devoted exploratory missions. These underground environments could provide protection from drastic temperature changes, radiation, and other extreme conditions on the Moon. However, they have only been observed by orbiters and little is known about their internal structure or suitability for habitation. Various ground-based robotic systems have been proposed to conduct an initial survey, but ground vehicles have a high risk of being immobilized on rough terrain. This paper introduces the concept and begins the development of an Autonomous Surveying Vehicle (ASV) as a candidate to explore these lava tubes. Although other vehicles have been previously proposed, the novelty of this concept lies in its compact design (<10kg), reusability, and safety. The ASV will feature a self-contained, refillable propulsion system that provides full mobility, allowing the vehicle to explore the lava tubes efficiently across multiple short-term surveying missions. The propulsion system will utilize low-pressure, inert cold gas to ensure safety for the user and avoid contamination of potential resources within the lava tubes. The vehicle will also be equipped with on-board sensors, such as inertial sensors and LiDAR, and an autonomous navigation system to simultaneously map and traverse the tubes. The ASV will be compact and inexpensive compared to other proposed systems, putting forth a simpler option for an initial survey of the tubes to determine whether a more extensive exploratory mission is warranted. These compact, low-pressure vehicles will allow astronauts or rovers to explore features in real-time, gather and process data in the field, and conduct repeated surveys on targets of interest. The ASVs will also be valuable for other surveying missions in above-ground environments that would otherwise be inaccessible or hazardous for rovers and humans. This study outlines the mission goals and requirements, begins the development of the cold gas propulsion system, and conducts lunar simulations to demonstrate the overall utility and feasibility of the concept.